Unveiling performance patterns: Analysis of employees' performance in public health centers in East Lombok District - Budiman, Budiman; Menap, Menap; Karjono, Karjono; Saimi, Saimi (Institute of Computer Science (IOCS), 2024)
Employee performance is closely tied to the support of the environment in striving for work achievements, thus the individual capabilities of human resources (HR) employees are crucial in achieving such success. The aim of this research is to analyze the performance of healthcare center (puskesmas) employees in East Lombok Regency. This research method utilizes a qualitative approach. The study was conducted from June to December 2023 in 5 representative healthcare centers namely Labuhan Haji, Krongkong, Kotaraja, Karang Baru, and Dasan Lekong. The research informants consisted of 5 individuals, with 3 as primary informants and 2 as supporting informants. Data was collected through group discussion forums. The results of this research indicate that employee performance in East Lombok is not satisfactory, as evidenced by patient complaints. Based on these findings, it is recommended that healthcare center employees should be open in all aspects to their environment, not only related to performance but also in communication, so that the relationship between employees and their environment can be well established.